Human Rhinovirus Species and Season of Infection Determine Illness Severity - Lee, Wai-Ming (American Thoracic Society, 2012)
Rationale: Human rhinoviruses (HRVs) consist of approximately 160 types that cause a wide range of clinical outcomes, including asymptomatic infections, common colds, and severe lower respiratory illnesses. Objectives: To identify factors that influence the severity of HRV illnesses. Methods: HRV species and types were determined in 1,445 nasal lavages that were prospectively collected from 209 infants participating in a birth cohort who had at least one HRV infection. Questionnaires were used during each illness to identify moderate to severe illnesses (MSI). Measurements and Main Results: Altogether, 670 HRV infections were identified, and 519 of them were solitary infections (only one HRV type). These 519 viruses belonged to 93 different types of three species: 49 A, 9 B, and 35 C types. HRV-A (odds ratio, 8.2) and HRV-C (odds ratio, 7.6) were more likely to cause MSI compared with HRV-B. In addition, HRV infections were 5- to 10-fold more likely to cause MSI in the winter months (P < 0.0001) compared with summer, in contrast to peak seasonal prevalence in spring and fall. When significant differences in host susceptibility to MSI (P = 0.004) were considered, strain-specific rates of HRV MSI ranged from less than 1% to more than 20%. Conclusions: Factors related to HRV species and type, season, and host susceptibility determine the risk of more severe HRV illness in infancy. These findings suggest that anti-HRV strategies should focus on HRV-A and -C species and identify the need for additional studies to determine mechanisms for seasonal increases of HRV severity, independent of viral prevalence, in cold weather months.